FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN GARUDAMILES PADA MASKAPAI PENERBANGAN GARUDA INDONESIA AIRWAYS DI PEKANBARU - Chendy Ifca; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of conduching this research is to know factors-factors affecting the costumer loyalty at airlines and for know dominant factors affecting costumer loyalty.This research used descriptive methode to analyze the probloms. The sampel of this research was 103 consist of 100 respondence and 3 key informant. From factors-factors affecting the costumer loyalty are 5 sub variable they are satisfaction, emotional bonding, trust, choice reduction and habit and history with company.Based on the result of this research, the respon of respondence agree with factors-factors affecting the costumer loyalty and the respon is very agree and loyalty, and the dominant factors is satisfaction.Key word : Costumer Loyalty, GarudaMiles, Garuda Indonesia